Investigação do fenômeno de auto-cicatrização de fissuras em microconcreto de alta performance reforçado com fibras de aço e sisal - Moreira, Tamara Nunes da Cunha (2017)
In this dissertation was studied the self-healing phenomenon of cement-slag microconcretes reinforced with volumetric fractions of short fibers (lf=13 mm) of steel and sisal of 1,0-1,28% and 0,28-0,64%, respectively. Crack opening of 200 µm were induced under direct tensile loads at 28 days of age in 30x60x300 mm specimens drawn from 30x600x900 mm slabs. Samples were conditioned in water (W) or wet and dry cycles (W&D) cycles for 3 and 6 months. Direct tensile tests were performed after conditioning and from the obtained results were calculated the load capacity recovery (IRT) and stiffness recovery (IRD) indexes. Thermogravimetric tests were performed to identify the phases present in the matrix and in the filler filling material. For the study of the fiber-matrix interface and the healing of microcracks formed in this region, a pre-slip of 200 µm of a steel fiber from the matrix was conducted and, after conditioning, pull-out tests was performed. Computed tomography determined the effect of the orientation/concentration of fibers along the thickness and length of the slab and that were correlated with the behavior in the direct tensile post-healing behaviour of the samples. The presence of the porous sisal fibers allowed a higher nucleation of hydrated products (CaCO3 and CAH) in the pre-induced cracks in direct tensile. Micro-cracks smaller than 60 µm were sealed resulting in IRT’s recovery. CT Scan results indicated a higher concentration of steel fibers in the lower third of the samples, resulting in smaller cracks and greater healing. Cracks of 200 µm located on the upper face of the samples showed partial sealing, affecting IRD performance.